2020
DOI: 10.53879/id.57.05.11657
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Nanospheres - Current Status

Abstract: Nanospheres are polymeric matrix of spherical shape that ranges in size between 10- 200 nm in diameter. The drug is dissolved, entrapped, encapsulated or attached to the matrix of polymer. The nature of nanospheres can be amorphous or crystalline, and they potentiate to protect the drug from chemical and enzymatic degradation. In the matrix of this polymer, a drug will evenly distribute as well as physically and uniformly disperse and can enclose a variety of drugs, enzymes and, genes, providing a long circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Rao et al synthesized some important oxovanadium(IV), Mn(II), Fe(II), Cu(II), Co(II), and Ni(II) metal complexes with a novel quadridentate ligand prepared from DHA and carbohydrazide. [ 93 ] The synthesized complexes were assayed in vitro for fungicidal activities against A. niger . All the tested compounds exhibited about 70.5 % to 100 % inhibition which is much better with than the ligand.…”
Section: Biological Activities Of Dha‐based Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rao et al synthesized some important oxovanadium(IV), Mn(II), Fe(II), Cu(II), Co(II), and Ni(II) metal complexes with a novel quadridentate ligand prepared from DHA and carbohydrazide. [ 93 ] The synthesized complexes were assayed in vitro for fungicidal activities against A. niger . All the tested compounds exhibited about 70.5 % to 100 % inhibition which is much better with than the ligand.…”
Section: Biological Activities Of Dha‐based Compoundsmentioning
confidence: 99%
“…DHA is also an effective chelating ligand that serves as a flexible precursor for synthesizing several metal complexes with significant pharmacological properties. [ 16,17 ] It was also noticed in most of the cases, the complexation of DHA derivatives with a metal atom led to significant enhancement in the activity. Several reports available in the literature showed that small structural changes in DHA can lead to more bioactive molecules with improved potency, decreased toxicity, more excellent metabolic stability, and bioavailability.…”
Section: Introductionmentioning
confidence: 98%